2017
DOI: 10.1149/2.0391711jes
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Scale Analysis of Liquid Water Breakthrough inside Gas Diffusion Layer for PEMFC Using X-ray Computed Tomography and Lattice Boltzmann Method

Abstract: The main objective of this work is to predict the breakthrough pressure of liquid water transport through the gas diffusion layer (GDL) and/or micro porous layer (MPL) used in polymer electrolyte membrane fuel cells. The integration of structural GDL and MPL with Lattice Boltzmann Method is primary focused. The numerical predictions are also compared with experimental data. The interaction between liquid phase and different surface treatments of solid structures controls the evolution of liquid water and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 74 publications
5
70
0
Order By: Relevance
“…Jeon and Kim [179] revealed that the compression ratio significantly affects the water transport in the GDL. Most recently, the transport of liquid water inside the GDL was revealed by using LBM [261,262]. The overall LBM predictions of water evolution within the GDL agree well with the in-situ flow visualization from X-ray CT. Zhang et al [68] proposed a 3D LBM to simulate liquid water transport in GDL of PEMFC with electrochemical reaction on the catalyst layer and oxygen diffusion in GDL taken into account in transient state.…”
Section: Accepted Manuscriptsupporting
confidence: 53%
See 1 more Smart Citation
“…Jeon and Kim [179] revealed that the compression ratio significantly affects the water transport in the GDL. Most recently, the transport of liquid water inside the GDL was revealed by using LBM [261,262]. The overall LBM predictions of water evolution within the GDL agree well with the in-situ flow visualization from X-ray CT. Zhang et al [68] proposed a 3D LBM to simulate liquid water transport in GDL of PEMFC with electrochemical reaction on the catalyst layer and oxygen diffusion in GDL taken into account in transient state.…”
Section: Accepted Manuscriptsupporting
confidence: 53%
“…Therefore no validation of the pore-scale modeling based on the CL structure has been made to compare the polarization curves from simulation and experimental measurement. Nonetheless, validation of the model based on the comparison of the effective diffusivity, effective conductivity [222] and water distribution in the GDL [261,262] have been attempted.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recently, great attention has been drawn to pore-scale (PS) modeling to overcome some of the shortcomings of VA GDL models, and improve our understanding of specific transport processes (see, e.g., [43][44][45][46][47][48][49][50][51][52][53][54][55] among others). Furthermore, PS models allow the characterization of effective properties that are extremely difficult to measure experimentally due to the small dimensions of GDLs [23,24,27,[56][57][58][59][60][61][62][63][64][65][66].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[43][44][45][46][47][48]51,56,61,62,[64][65][66][67]71 Using XCT for membrane analysis is more challegning given the relatively low X-ray attenuation of the polymer. Garzon et al 68 demonstrated that Pt redistribution from the electrodes into the membrane can be captured by XCT.…”
mentioning
confidence: 99%